Utjecaj ugljik (IV) - oksida na promjene životne sredine - Džanić, Husein; Džanić, Fatmir (Promet - Traffic&Transportation, 2012)
This paper deals with the impacts of carbon oxides (C02) from motor exhaust emissions upon changes in the environment, warming up of the Earth and changes of regional and global climate. It has been established that the average annual emission from natural sources is 700 to 1000 x J09 tons of carbon oxides in conjunction with additional 30 x 109 tons introduced by human activities in burning fossil fuels of which some 17. 9 draw origin from mo tor traffic. Global annual concentrations of C02 increases by approximately 0,2% because human beings obtain some 90% of their power needs from burning fossil fuels. It has been established that in the world road motor vehicles emit 7,62 x 109 tons of co2 out of the total emission which is about 42,57 x l 09 tons in the year 1988. Road motor vehicles in Yugoslavia pollute the atmosphere with 21,41% x 106 tons with the annual increase of l, 78% and share in global pollution of 0,28% C02. In this pol1ution Croatia participates with 5,65 x 1()6 tons with the annual increase of 4,19% and its share in global pollution of 0,074% co2 . The author recommends gradual decrease of co2-emission by 50% through reduction of concentrations of 400 ppm in the air to the maximum which may only be attained by substitution in the consumption of fossil fuels. In road traffic gasoline and diesel fuels can successfully be substituted by hydrogen and thus help avoiding inevitable catastrophic consequences in the Earth's biosphere.